Intertruncal versus classical approach to supraclavicular brachial plexus block on sensory-motor blockade for upper extremity surgery: a randomized controlled non-inferiority trial - Zhipeng Wang; Jinyan Guo; Hanbin Xie; Guoliang Sun; Jianqiang Guan; Weifeng Yao; Quehua Luo (Korean Journal of Anesthesiology)
Background As the characteristics of the intertruncal approach to the supraclavicular block (IA-SCB) are uncertain, we aimed to compare its effect on sensory-motor blockade with that of the classical approach (CA) within 30 min post-block. Methods In total, 122 patients undergoing elbow, forearm, wrist, or hand surgery were randomly assigned to receive CA-SCB or IA-SCB. Both groups received identical local anesthetic agents (1% lidocaine and 0.5% ropivacaine) in 25 ml total. The IA-SCB group received 15 ml between the middle and inferior trunks and 10 ml between the superior and middle trunks, while the CA-SCB group received 15 ml in the corner pocket and 10 ml in the center of the neural clusters. Sensory-motor blockade of all four terminal nerves was assessed every 5 min for 30 min. The non-inferiority threshold aimed to exclude the possibility that the IA-SCB was > 5% inferior to the CA-SCB in terms of the proportion of patients with complete sensory blockade at 20 min post-block. Results Complete sensory blockade at 20 min post-block was 79.3% and 72.7% with the CA-SCB and IA-SCB, respectively, exceeding the non-inferiority margin of –5% (–6.6%, 95% CI [–22.3% to 9.1%]; P value for non-inferiority = 0.206). Additionally, the IA-SCB showed an inferior musculocutaneous nerve blockade, longer performance time, and higher incidence of hemidiaphragmatic paresis. Conclusions Our findings do not confirm the non-inferiority of the IA-SCB to the CA-SCB in achieving complete sensory blockade at 20 min post-block. Further research may be necessary to establish its efficacy in regional anesthesia.